Pengaruh Lingkungan Kerja, Kompetensi dan Etos Kerja Terhadap Kinerja Karyawan (Studi Pada Karyawan UMKM Tahu Kres KWB) - Amrullah, Angkoso Ahmad; Sunaryo, Hadi; Suharto, M. Khoirul Anwarudin Broto (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to examine and explain the influence of the work environment, competence and work ethic on employee performance at KWB Tahu Kres UMKM. The sample used in this study were 31 employees using the saturated sample technique. The data analysis method used in this study is quantitative data analysis using multiple linear regression analysis. Testing the data used is testing the simultaneous hypothesis (Test F) and testing the partial hypothesis (Test t). The results of this study indicate that simultaneously (Test F) the variables of the work environment, competence and work ethic have a significant effect on employee performance at the UKM Tahu Kres KWB. Meanwhile, based on the results of the partial test (t test) the work environment variable has a significant effect on employee performance at the UMKM Tahu Kres KWB, the competency variable has a significant effect on the performance of employees at the UMKM Tahu Kres KWB, the work ethic variable has a significant effect on the performance of employees at the UMKM Tahu Kres KWB. Keywords: Work Environment, Competence, Work Ethic and Employee Performance